Peer Learning in Instrumental Practicing - Nielsen, Siw G.; Johansen, Guro G.; Jørgensen, Harald (Frontiers in Psychology, 2018)
In higher music education (HME), the notion of “private teaching, private learning” has a long tradition, where the learning part rests on the student´s individual practising between instrumental lessons. However, recent research suggests that collaborative learning among peers is beneficial in several aspects, such as sense of belonging, motivation and self-efficacy. This is consistent with the concept of vicarious learning. In this study, we conducted a survey among bachelor music students in church music, performance or music education programs enrolled in a music academy (N = 96), where parts of the questionnaire addressed peer learning and peer´s influence on the students´s instrumental practising, and the degree of satisfaction with their practising. These issues were seen in relation to gender, musical genre and study program. Overall, the students reported engaging in peer learning related to their instrumental practising, to various degrees. This involved discussing practising matters with peers, and practising together with peers. However, student´s reports of their views on peer learning, show that they perceive it more beneficial than the amount of time reported doing it would indicate. No significant gender differences were found, but students within improvised music/jazz engaged the most in peer learning, and church music students the least. Neither the degree of engaging in peer learning nor reported influence from peers correlated significantly with the degree of satisfaction. We discuss whether a general dissatisfaction is caused by being in a competitive learning environment combined with a privatized culture for learning. Finally, we suggest that collaborative forums for instrumental practising within HME institutions can function as constructive and supportive arenas to enhance students learning and inner motivation.